Multiphase composite coated high-dielectric-constant ceramic material and preparation method thereof

By adding holmium oxide and optimizing the ball milling and sintering processes, a multiphase composite encapsulated high dielectric constant ceramic material was prepared, solving the problems of insufficient oxygen vacancy control and narrow sintering process, and realizing a ceramic material with high dielectric constant, low dielectric loss and good mechanical properties.

CN121063931APending Publication Date: 2025-12-05YUANLIU HONGYUAN (SUZHOU) ELECTRONIC TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511152105.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-18
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing high dielectric constant ceramic materials suffer from problems such as insufficient oxygen vacancy regulation, narrow sintering process window, and low powder homogenization efficiency, resulting in high dielectric loss, unstable performance, and significant microstructural heterogeneity.

Method used

A method for preparing multiphase composite-encapsulated high dielectric constant ceramic materials is adopted. Holmium oxide is added as a rare earth modifier, and the ball milling process and sintering temperature are optimized to ensure powder uniformity and densification effect. This includes specific components and process steps such as ball milling, drying, forming and sintering.

Benefits of technology

It significantly improves the dielectric constant, reduces dielectric loss, enhances the densification and mechanical properties of the material, and ensures the consistency of the material's microstructure and overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121063931A_ABST
    Figure CN121063931A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of synthesis and processing of ceramic materials, and discloses a multiphase composite coated high-dielectric-constant ceramic material and a preparation method of the multiphase composite coated high-dielectric-constant ceramic material. 11%-13% of strontium titanate; 5%-7% of holmium oxide; 5%-6% of lead magnesium niobate; 6%-7% of titanium dioxide; 2%-3% of yttrium oxide; 3%-4% of magnesium oxide; 3%-4% of bismuth oxide; 2%-3% of lithium carbonate; 4%-5.5% of silicon dioxide; 1%-2% of zinc oxide; 2.5%-3.5% of manganese dioxide; 6%-7% of copper oxide; 3%-4% of glass powder; 0.05% to 0.08% of lanthanide series elements; through the steps of component pretreatment, ball milling and mixing, drying and sieving, forming, sintering and post-treatment, the component activity is improved through high-temperature calcination pretreatment, and directional growth of crystal grains in the components can be promoted by precisely controlled sintering temperature; the prepared ceramic material has the advantages of high dielectric constant, low dielectric loss, excellent densification effect and good mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of synthesis and processing of ceramic materials, in particular to a multi-phase composite wrapped high dielectric constant ceramic material and a preparation method thereof. BACKGROUND

[0002] In the prior art, there are three major technical bottlenecks in the preparation of high dielectric constant ceramic materials: first, the traditional formula lacks effective means to control oxygen vacancies, resulting in dense lattice defects and high dielectric loss; second, the sintering process window is narrow, and it is difficult to balance densification and phase composition stability, especially for multi-component systems containing lead magnesium niobate (PMN), low-temperature sintering easily causes poor grain boundary development and pore residue; third, the powder homogenization efficiency is low, and conventional ball milling process cannot achieve uniform dispersion at the nanoscale, resulting in significant microstructure heterogeneity of the sintered body. These problems directly restrict the dielectric response efficiency and mechanical reliability of the material. For example, the baseline formula without the addition of rare earth modifiers usually shows low dielectric constant, high loss factor, and large performance fluctuations in a wide temperature range. In addition, short-time ball milling in ethanol medium commonly used in industrial production can speed up the drying speed, but it easily leads to particle agglomeration and composition segregation, further deteriorating the consistency of the material. SUMMARY

[0003] (I) Technical problems solved

[0004] In view of the deficiencies of the prior art, the present application provides a multi-phase composite wrapped high dielectric constant ceramic material and a preparation method thereof, which has the advantages of high dielectric constant, low dielectric loss, excellent densification effect and good mechanical properties, solving the problems of insufficient oxygen vacancy control in traditional formula, narrow sintering process window and low powder homogenization efficiency.

[0005] (II) Technical solutions

[0006] To achieve the above-mentioned purpose, the present application provides the following technical solutions: a multi-phase composite wrapped high dielectric constant ceramic material, the composition and mass ratio of the ceramic material are as follows: barium titanate 16%-19%; strontium titanate 11%-13%; holmium oxide 5%-7%; lead magnesium niobate 5%-6%; titanium dioxide 6%-7%; yttrium oxide 2%-3%; magnesium oxide 3%-4%; bismuth oxide 3%-4%; lithium carbonate 2%-3%; silicon dioxide 4%-5.5%; zinc oxide 1%-2%; manganese dioxide 2.5%-3.5%; copper oxide 6%-7%; glass powder 3%-4%; lanthanide elements 0.05%-0.08%; binder 3%-5%.

[0007] Preferably, the barium titanate is prepared from barium carbonate and titanium dioxide, and the chemical reaction formula is:

[0008] BaCO 3(S)+TiO 2(S) BaTiO 3(S) +CO 2(g)

[0009] BaCO3+TiO2+CO2→BaTiO3(s)+CO2(g) Δ

[0010] Preferably, the lead magnesium niobate is prepared from lead oxide, magnesium oxide and niobium pentoxide, and the chemical reaction formula is as follows:

[0011] PbO+MgO+Nb2O5→Pb(Mg1 / 3Nb2 / 3)O3(s) Δ (S) +MgO (S) +Nb2O 5(S) Pb(Mg1 / 3Nb2 / 3)O3(s) Δ 3(S)

[0012] Nb2O5+MgO+PbO→Pb(Mg1 / 3Nb2 / 3)O3(s) Δ

[0013] Preferably, the glass powder is borosilicate glass, with a softening point of 650-750℃, a thermal expansion coefficient of 4.5-5.5×10 -6 / K, and a particle size of 0.5-3μm.

[0014] Preferably, the lanthanide series elements are composed of lanthanum oxide, neodymium oxide and praseodymium oxide in a ratio of 1:1:2.

[0015] A preparation method of a multiphase composite wrapped high dielectric constant ceramic material, according to the composition and mass ratio of the multiphase composite wrapped high dielectric constant ceramic material, comprises the following preparation steps:

[0016] Step one, preparing the formula components: preparing the formula proportion of barium titanate, strontium titanate, holmium oxide, lead magnesium niobate, titanium dioxide, yttrium oxide, magnesium oxide, bismuth oxide, lithium carbonate, silicon dioxide, zinc oxide, manganese dioxide, copper oxide, glass powder, lanthanide series elements and binder;

[0017] Step two, component pretreatment: pretreating the barium titanate, strontium titanate, lead magnesium niobate, titanium dioxide and glass powder;

[0018] ​​Step three, ball milling mixing: the pretreated barium titanate, strontium titanate, lead magnesium niobate, titanium dioxide and glass powder, and the proportion of holmium oxide, yttrium oxide, magnesium oxide, bismuth oxide, lithium carbonate, silicon dioxide, zinc oxide, manganese dioxide, copper oxide and lanthanide elements are put into a ball mill, 30%-40% of the total mass of all solid materials is added as a dispersion medium, and the binder is added at a rate of 10-15 mL / min. The ball-to-material ratio and ball milling time are set to ball mill, so that all components are fully mixed and uniform, and a mixed slurry is obtained;

[0019] Step four, drying and sieving: the mixed slurry after ball milling is placed in a drying device and dried at a set temperature to obtain a dried mixed powder. The dried powder is sieved;

[0020] Step five, forming: the sieved mixed powder is placed in a mold and pressed under the set conditions to obtain a formed ceramic body;

[0021] Step six, sintering: the formed ceramic body is placed in a sintering furnace and sintered under the set conditions to form a ceramic material;

[0022] Step seven, post-processing: the sintered ceramic material is subjected to cutting, grinding and polishing post-processing, and the performance of the ceramic material is tested.

[0023] Preferably, in step two, the barium titanate and strontium titanate are calcined at a temperature of 850-900℃ for 2-3h for pretreatment; the lead magnesium niobate is calcined at a temperature of 750-800℃ for 1-2h; the titanium dioxide is calcined at 550-600℃ for 1-2h; and the glass powder is dried at 100-120℃ for 4-6h.

[0024] Preferably, in step three, the ball milling conditions are: zirconium oxide balls are used as the grinding medium, the ball-to-material ratio is 5:1-8:1, the ball milling speed is 300-500r / min, and the ball milling time is 6-10 hours; During ball milling, stir every 1-2 hours; After ball milling, the solid content of the slurry is controlled at 60%-70%.

[0025] Preferably, in step four, the drying and sieving conditions are: the drying temperature is 80-120℃, the drying time is 10-14 hours, the vacuum drying method is used, and the vacuum degree is controlled at 0.08-0.1MPa during vacuum drying; The dried powder is sieved through a 100-150 mesh sieve.

[0026] Preferably, the forming conditions in the step five are: using dry pressing forming method, the forming pressure is 150-200MPa, the pressure maintaining time is 8-15 minutes; the mold material selects high-strength steel with tensile strength greater than or equal to 600MPa, and 0.05-0.1g / dm 2 range of zinc stearate is applied on the inner wall of the mold; the green compact density after forming is measured to be between 73%-74%;

[0027] The sintering conditions in the step six are: the sintering temperature range is 1300-1350℃, the sintering holding time is 3-4 hours, the heating rate is controlled to be 5-8℃ / min, the oxygen atmosphere in the furnace is maintained during the sintering process, the oxygen flow is 0.5-1L / min, and the temperature is decreased to room temperature at a rate of 3-5℃ / min after the sintering is completed.

[0028] Compared with the prior art, the application provides a multi-phase composite wrapped high dielectric constant ceramic material and a preparation method thereof, and has the following beneficial effects:

[0029] 1. The application adds holmium oxide to improve the dielectric performance, and holmium oxide as a core rare earth modifier can effectively inhibit the migration of oxygen vacancies by replacing lattice sites and refine the grain structure, and a series of action mechanisms can significantly improve the dielectric constant of the ceramic material and greatly reduce the dielectric loss, compared with the formula without adding holmium oxide in the traditional preparation process, the dielectric constant of the ceramic material of the application is greatly improved, and the loss rate is also obviously reduced.

[0030] 2. The application optimizes the sintering temperature to improve the densification and comprehensive performance of the material, and the sintering temperature is accurately controlled at 1300-1350℃ to ensure the densification of the ceramic material, and a lower sintering temperature will lead to insufficient densification of the material and incomplete development of the grain boundary, thereby reducing the dielectric constant, bending strength and bulk density, therefore, the high-temperature sintering of 1300-1350℃ in the application can improve the densification degree of the ceramic material.

[0031] 3. The application optimizes the ball milling process to improve the uniformity of the powder and the consistency of the sintered body, and the ball milling process is optimized and water medium ball milling is used for 6-10 hours to ensure the uniformity of the powder and the consistency of the microstructure of the sintered body, and shortening the ball milling time or using ethanol medium will lead to a decrease in the uniformity of the powder, segregation of the sintered body components and an increase in the porosity, which will reduce the dielectric constant and increase the loss, therefore, the optimized ball milling process of the application can improve the comprehensive performance of the ceramic material. BRIEF DESCRIPTION OF DRAWINGS

[0032] Figure 1 The preparation flowchart of the application is shown in the following. DETAILED DESCRIPTION

[0033] With reference to the drawings of the embodiments of the present application, the technical solutions in the embodiments of the present application will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by those of ordinary skill in the art without creative work fall within the protection scope of the present application.

[0034] Please refer to Figure 1 A multi-phase composite wrapped high dielectric constant ceramic material, the composition and mass ratio of the ceramic material are as follows: barium titanate (BaTiO3) 16%-19%; strontium titanate (SrTiO3) 11%-13%; holmium oxide (Ho2O3) 5%-7%; lead magnesium niobate (PMN) 5%-6%; titanium dioxide (TiO2) 6%-7%; yttrium oxide (Y2O3) 2%-3%; magnesium oxide 3%-4%; bismuth oxide (Bi2O3) 3%-4%; lithium carbonate (Li2CO3) 2%-3%; silicon dioxide 4%-5.5%; zinc oxide 1%-2%; manganese dioxide (MnO2) 2.5%-3.5%; copper oxide 6%-7%; glass powder 3%-4%; lanthanide 0.05%-0.08%; binder 3%-5%.

[0035] Specifically, the roles of various components in the ceramic material are as follows:

[0036] Table 1

[0037] Ingredients Mass ratio range Core role Mechanism of action Barium titanate 16%~19% Main dielectric phase matrix Provide ferroelectric basis, dominate spontaneous polarization, determine dielectric constant peak Strontium titanate 11%~13% Dielectric performance modifier Broaden Curie peak, improve temperature stability, reduce loss Holmium oxide 5%~7% Rare earth modifier (core) Ho 3+ substitutional lattice sites, suppress oxygen vacancy migration, refine grains, and increase dielectric constant Lead magnesium niobate 5%~6% Relaxor ferroelectric additive phase Introduce dispersion phase change, broaden dielectric temperature curve, enhance dielectric response Titanium dioxide 6%~7% Titanium source supplement Compensate for sintering titanium volatilization, promote grain growth, adjust lattice distortion Yttrium oxide 2%~3% Grain boundary modifier Y 3+ rich grain boundary, inhibit abnormal grain growth, and improve the breakdown field strength Magnesium oxide 3%~4% Sintering aid + mechanical reinforcing agent Reduce sintering temperature, improve density, enhance bending strength Bismuth oxide 3%~4% Liquid phase wrapping promoter Low temperature liquid phase formation, promote densification, wrap grain to form core-shell structure (key wrapping phase) Lithium carbonate 2%~3% Low temperature sintering agent Decomposes to Li2O, lowers melting point, accelerates diffusion kinetics <!-- 3 -->]]> Silicon dioxide 4%~5.5% Glass phase former Form glass network with bismuth oxide, fill pores, improve insulation Zinc oxide 1%~2% Pressure-sensitive characteristic modifier Improve grain boundary barrier uniformity, optimize nonlinear conductance characteristics Manganese dioxide 2.5%~3.5% Oxygen vacancy inhibitor Mn 4+ / Mn 2+ Variable absorption of oxygen vacancies, reducing dielectric loss Copper oxide 6%~7% Fluxing agent + grain boundary modifier Promote grain boundary glass phase flow, reduce sintering temperature (1300°C→1250°C operable) Glass powder 3%~4% Wrapping phase skeleton Pre-melted glass phase accelerates densification, wraps main crystal phase to inhibit grain boundary migration (key to realizing "wrapping type" structure) Lanthanide elements 0.05%~0.08% Grain boundary activator Trace La / Ce doping optimizes grain boundary barrier height, improves insulation resistance Binder 3%~5% Molding aid Improve powder molding plasticity, completely volatilize during sintering

[0038] Specifically, barium titanate is prepared from barium carbonate (BaCO3) and titanium dioxide (TiO2), and the chemical reaction formula is as follows:

[0039] BaCO 3(S) +TiO 2(S) BaTiO 3(S) +CO 2(g)

[0040] In the formula, BaCO3 represents barium carbonate as a barium source, TiO2 represents titanium dioxide as a titanium source, BaTiO3 represents barium titanate as a target product, CO2 represents carbon dioxide as a byproduct of reaction, (s) represents solid state, (g) represents gaseous state, Δ represents high-temperature reaction, and the reaction temperature is ≥ 1100°C.

[0041] Specifically, lead magnesium niobate is prepared from lead oxide (PbO), magnesium oxide and niobium pentoxide (Nb2O5), and the chemical reaction formula is as follows:

[0042] PbO (S) +MgO (S) +Nb2O 5(S) Pb(O) )O 3(S)

[0043] In the formula, Nb2O5 represents di-niobium pentoxide as a niobium source, MgO represents magnesium oxide as a magnesium source, PbO represents lead oxide as a lead source, Pb(O)3 represents lead magnesium niobate, which is a target product, (s) represents a solid state, and Δ represents a solid phase reaction, and the reaction temperature is between 850-900℃.

[0044] Specifically, the glass powder is borosilicate glass (B2O3-SiO2-ZnO system), the softening point is 650-750℃, the thermal expansion coefficient is 4.5-5.5×10 -6 / K, and the particle size is between 0.5-3μm.

[0045] Specifically, the lanthanide series element is composed of lanthanum oxide (La2O3), neodymium oxide (Nd2O3) and praseodymium oxide (Pr6O 11 ) in a ratio of 1:1:2.

[0046] A preparation method of a multiphase composite wrapped high dielectric constant ceramic material is prepared according to the composition and mass ratio of the multiphase composite wrapped high dielectric constant ceramic material, comprising the following preparation steps:

[0047] Step one, preparing the formula composition: preparing the formula proportion of barium titanate, strontium titanate, holmium oxide, lead magnesium niobate, titanium dioxide, yttrium oxide, magnesium oxide, bismuth oxide, lithium carbonate, silicon dioxide, zinc oxide, manganese dioxide, copper oxide, glass powder, lanthanide series element and binder;

[0048] Step two, component pretreatment: pretreating the barium titanate, strontium titanate, lead magnesium niobate, titanium dioxide and glass powder;

[0049] Step three, ball milling mixing: putting the pretreated barium titanate, strontium titanate, lead magnesium niobate, titanium dioxide and glass powder, and the formula proportion of holmium oxide, yttrium oxide, magnesium oxide, bismuth oxide, lithium carbonate, silicon dioxide, zinc oxide, manganese dioxide, copper oxide and lanthanide series element into a ball mill, adding 30%-40% of deionized water as a dispersion medium based on the total mass of all solid materials, slowly adding the binder at a rate of 10-15mL / min, setting the ball-to-material ratio and ball milling time for ball milling, so that all components are fully mixed and uniform, to obtain a mixed slurry;

[0050] Step four, drying and sieving: putting the mixed slurry after ball milling into a drying device to remove the water in the slurry at a set temperature to obtain a dried mixed powder, and sieving the dried powder to ensure uniform powder particle size; ​

[0051] Step five, forming: the mixed powder after screening is put into the mold, and the pressing is carried out under the set conditions to obtain the formed ceramic body;

[0052] Step six, sintering: the formed ceramic body is put into the sintering furnace, and sintering is carried out under the set conditions to make the particles in the ceramic body adhere and diffuse to form a dense ceramic material;

[0053] Step seven, post-processing: the sintered ceramic material is subjected to post-processing such as cutting, grinding and polishing to obtain the required size accuracy and surface quality, and at the same time, the performance test of the ceramic material is carried out to ensure that it meets the related performance indicators such as high dielectric constant.

[0054] Specifically, in step two, barium titanate and strontium titanate are calcined at a temperature of 850-900℃ for 2-3h for pretreatment to remove impurities and improve activity; lead magnesium niobate is calcined at a temperature of 750-800℃ for 1-2h to reduce internal defects; titanium dioxide is calcined at 550-600℃ for 1-2h to improve its purity and reactivity; glass powder is dried at 100-120℃ for 4-6h to remove moisture and prevent bubbles from being generated in the subsequent process.

[0055] Specifically, in step three, the ball milling mixing conditions are as follows: zirconia balls are used as grinding medium, the ball-to-material ratio is 5:1-8:1, the ball milling speed is 300-500r / min, and the ball milling time is 6-10 hours; during the ball milling process, the slurry is stirred every 1-2 hours to prevent sedimentation; after the ball milling, the solid content of the slurry is controlled at 60%-70%.

[0056] Specifically, in step four, the drying and screening conditions are as follows: the drying temperature is 80-120℃, the drying time is 10-14 hours, the vacuum drying method is used, and the vacuum degree is controlled at 0.08-0.1MPa during vacuum drying; the dried powder is screened through a 100-150 mesh sieve to ensure that the powder is not clumped and the particle size distribution is uniform.

[0057] Specifically, in step five, the forming conditions are as follows: the dry pressing forming method is used, the forming pressure is 150-200MPa, and the pressure holding time is 8-15 minutes; the mold material is high-strength steel with a tensile strength ≥600MPa, and 0.05-0.1g / dm² of zinc stearate is applied on the inner wall of the mold to facilitate the removal of the body; the density of the formed body is measured to be between 73%-74%, and the body surface should be flat, crack-free and angle-free.

[0058] Specifically, the sintering conditions in step six are: the sintering temperature range is 1300-1350℃, and the appropriate temperature can be selected according to the actual situation for different systems; the sintering holding time is 3-4 hours, which can be adjusted according to the material composition and sintering temperature; the heating rate is controlled at 5-8℃ / min to avoid cracks in the ceramic body due to too fast heating; the oxygen atmosphere in the furnace is maintained during sintering, and the oxygen flow is 0.5-1L / min, which helps to improve the material density; after sintering, the temperature is lowered to room temperature at a rate of 3-5℃ / min to ensure the stability of the ceramic material structure.

[0059] Example 1

[0060] The composition and mass percentage of the ceramic material are: barium titanate 16%, strontium titanate 13%, holmium oxide 5%, lead magnesium niobate 6%, titanium dioxide 6%, yttrium oxide 3%, magnesium oxide 3%, bismuth oxide 4%, lithium carbonate 2%, silicon dioxide 4%, zinc oxide 1%, manganese dioxide 2.5%, copper oxide 6%, glass powder 3%, lanthanide elements 0.05%, and binder 3%.

[0061] The raw materials are accurately weighed according to the above ratio, mixed uniformly, and then subjected to ball milling treatment, with a ball milling time of 12 hours and deionized water as the ball milling medium. After ball milling, the powder is dried to obtain a powder; the powder is then pre-fired at 800℃ for 2 hours, and then pressed into a shape with a forming pressure of 100MPa; finally, the formed body is placed in a sintering furnace and sintered at 1300℃ for 4 hours, and then cooled in the furnace to obtain a ceramic material.

[0062] Comparative Example 1

[0063] The composition and mass percentage of the ceramic material are: barium titanate 17%, strontium titanate 12%, no holmium oxide, lead magnesium niobate 5.5%, titanium dioxide 6.5%, yttrium oxide 2.5%, magnesium oxide 3.5%, bismuth oxide 3.5%, lithium carbonate 2.5%, silicon dioxide 4.5%, zinc oxide 1.5%, manganese dioxide 3%, copper oxide 6.5%, glass powder 3.5%, lanthanide elements 0.06%, and binder 4%.

[0064] Preparation process: the raw materials are accurately weighed according to the above ratio, mixed uniformly, and then subjected to ball milling treatment, with a ball milling time of 9 hours and deionized water as the ball milling medium. After ball milling, the powder is dried to obtain a powder; the powder is then pre-fired at 780℃ for 2.5 hours, and then pressed into a shape with a forming pressure of 110MPa; finally, the formed body is placed in a sintering furnace and sintered at 1320℃ for 3.5 hours, and then cooled in the furnace to obtain a ceramic material.

[0065] By removing the key rare earth modifier holmium oxide, the influence on dielectric properties and sintering is observed, and the total amount of the composition is balanced by slightly increasing the main matrix.

[0066] Example 2

[0067] The ceramic material has the following components and mass percentages: barium titanate 19%, strontium titanate 11%, holmium oxide 7%, lead magnesium niobate 5%, titanium dioxide 7%, yttrium oxide 2%, magnesium oxide 4%, bismuth oxide 3%, lithium carbonate 3%, silicon dioxide 5.5%, zinc oxide 2%, manganese dioxide 3.5%, copper oxide 7%, glass powder 4%, lanthanide element 0.08%, and binder 5%.

[0068] The raw materials are accurately weighed according to the above-mentioned ratio, mixed uniformly, and then subjected to ball milling treatment, the ball milling time is 6 hours, the ball milling medium is ethanol, and the powder is obtained after drying; the powder is pre-fired at 750°C for 3 hours, then pressed into shape, the forming pressure is 120 MPa; finally, the shaped body is placed into a sintering furnace, sintered at 1350°C for 3 hours, and the ceramic material is obtained after cooling in the furnace.

[0069] Comparative Example 2

[0070] The ceramic material has the following components and mass percentages: barium titanate 19%, strontium titanate 11%, holmium oxide 7%, lead magnesium niobate 5%, titanium dioxide 7%, yttrium oxide 2%, magnesium oxide 4%, bismuth oxide 3%, lithium carbonate 3%, silicon dioxide 5.5%, zinc oxide 2%, manganese dioxide 3.5%, copper oxide 7%, glass powder 4%, lanthanide element 0.08%, and binder 5%.

[0071] Preparation process: the raw materials are accurately weighed according to the above-mentioned ratio, mixed uniformly, and then subjected to ball milling treatment, the ball milling time is 3 hours, the ball milling medium is ethanol, and the powder is obtained after drying; the powder is pre-fired at 750°C for 3 hours, then pressed into shape, the forming pressure is 120 MPa; finally, the shaped body is placed into a sintering furnace, sintered at 1250°C for 3 hours, and the ceramic material is obtained after cooling in the furnace.

[0072] By using the exact same formula as in Example 2, but significantly reducing the sintering temperature (1250°C vs. 1350°C), the effect of insufficient sintering temperature on the density, strength and dielectric properties of the material is investigated.

[0073] Example 3

[0074] The ceramic material has the following components and mass percentages: barium titanate 19%, strontium titanate 11%, holmium oxide 7%, lead magnesium niobate 5%, titanium dioxide 7%, yttrium oxide 2%, magnesium oxide 4%, bismuth oxide 3%, lithium carbonate 3%, silicon dioxide 5.5%, zinc oxide 2%, manganese dioxide 3.5%, copper oxide 7%, glass powder 4%, lanthanide element 0.08%, and binder 5%.

[0075] The raw materials are accurately weighed according to the above-mentioned ratio, mixed uniformly, and then subjected to ball milling treatment, the ball milling time is 10 hours, the ball milling medium is deionized water, and the powder is obtained after drying; the powder is pre-fired at 780 DEG C for 2.5 hours, then pressed into shape, the forming pressure is 110 MPa; finally, the shaped body is put into a sintering furnace, sintered at 1320 DEG C for 3.5 hours, and cooled in the furnace to obtain the ceramic material.

[0076] Comparative Example 3

[0077] The components and mass percentages of the ceramic material are: barium titanate 16%, strontium titanate 13%, holmium oxide 5%, lead magnesium niobate 6%, titanium dioxide 6%, yttrium oxide 3%, magnesium oxide 3%, bismuth oxide 4%, lithium carbonate 2%, silicon dioxide 4%, zinc oxide 1%, manganese dioxide 2.5%, copper oxide 6%, glass powder 3%, lanthanide 0.05%, and binder 3%.

[0078] Preparation process: accurately weigh each raw material according to the above-mentioned ratio, mix uniformly, and then perform ball milling treatment, the ball milling time is 3 hours, the ball milling medium is ethanol, and the powder is obtained after drying; the powder is pre-fired at 800 DEG C for 2 hours, then pressed into shape, the forming pressure is 100 MPa; finally, the shaped body is put into a sintering furnace, sintered at 1300 DEG C for 4 hours, and cooled in the furnace to obtain the ceramic material.

[0079] By using the exact same formula as Example 3, but shortening the ball milling time (10 hours vs. 3 hours) and changing the ball milling medium (ethanol vs. water), the effects of powder mixing uniformity and particle size distribution on the microstructure and performance of the final sintered body are investigated.

[0080] The formula components of the examples and comparative examples are made into ceramic materials, and the ceramic materials are tested for performance, and the test data are as follows in Table 2:

[0081] Comparative Table 2 of ceramic material performance test

[0082] Sample Dielectric constant (1 kHz, 25°C) Dielectric loss (tan δ, %, 1 kHz) Bending strength (MPa) Bulk density (g / cm³) Insulation resistivity (Ω·cm, 100V DC) Example 1 28,500 1.2 155 5.85 3.5 x 10 12 ]]> Comparative Example 1 18,200 2.9 132 5.70 8.2 x 10 11 ]]> Example 2 31,800 0.9 168 5.93 5.1 x 10 12 ]]> Comparative Example 2 20,100 3.8 118 5.55 1.8 x 10 11 ]]> Example 3 29,600 1.0 162 5.89 4.3 x 10 12 ]]> Comparative Example 3 24,300 1.9 142 5.76 1.4 x 10 12 ]]>

[0083] From Table 2, it is analyzed that:

[0084] (1) The role of holmium oxide (comparative example 1 vs. examples 1-3): after removing holmium oxide, the dielectric constant of the ceramic material prepared from the formula components of comparative example 1 decreases by 36.1% compared with example 1, and the loss increases by 141.7%, which proves that rare earth elements are crucial for improving polarization rate and suppressing grain boundary defects.

[0085] (2) Sintering temperature effect (comparing example 2 with comparative example 2): in comparative example 2, due to the sintering temperature of 1250 DEG C, the density of the ceramic material prepared thereby is decreased by 6.4%, the strength is decreased by 29.8%, and the dielectric constant is decreased by 36.8%. The comparison shows that decreasing the sintering temperature will result in insufficient densification of the ceramic material and incomplete development of the grain boundary.

[0086] (3) Ball milling process effect (comparing example 3 with example 1): in comparative example 3, due to the shortened ball milling time and ethanol medium, the dielectric constant of the ceramic material prepared thereby is decreased by 14.7%, and the loss is increased by 58.3%. This reflects that the lack of the ball milling process step will result in decreased powder uniformity, increased segregation of the sintered body components and increased porosity of the ceramic material.

[0087] Summary: the holmium oxide in the formula component is the core modifier for improving the dielectric properties of the multiphase composite wrapped high dielectric constant ceramic material, and can inhibit oxygen vacancies and refine the grain size. The sintering temperature of 1350 DEG C can improve the density of the lead magnesium niobate body, and the low temperature sintering in comparative example 2 will result in significant degradation of the density. The 6-hour water medium ball milling (compared with 3-hour ethanol) can guarantee the powder uniformity, which directly affects the consistency of the microstructure of the sintered body. The comprehensive performance of example 3 is the best (the dielectric loss is the lowest and the strength is balanced), and the process parameters (sintering at 1320 DEG C + 10h ball milling) are the best combination.

[0088] Although the embodiments of the present application have been shown and described, it is to be understood that various changes, modifications, substitutions and alterations can be made to the embodiments without departing from the principles and spirit of the present application, and the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A multiphase composite wrapped high dielectric constant ceramic material, characterized by, The ceramic material is composed of barium titanate 16%-19%, strontium titanate 11%-13%, holmium oxide 5%-7%, lead magnesium niobate 5%-6%, titanium dioxide 6%-7%, yttrium oxide 2%-3%, magnesium oxide 3%-4%, bismuth oxide 3%-4%, lithium carbonate 2%-3%, silicon dioxide 4%-5.5%, zinc oxide 1%-2%, manganese dioxide 2.5%-3.5%, copper oxide 6%-7%, glass powder 3%-4%, lanthanide elements 0.05%-0.08%, and binder 3%-5%.

2. The multiphase composite wrapped high dielectric constant ceramic material of claim 1, wherein: The barium titanate is prepared from barium carbonate and titanium dioxide, and the chemical reaction formula is as follows: BaCO 3(S) +TiO 2(S) BaTiO 3(S) +CO 2(g) In the formula, BaCO3 represents barium carbonate as a barium source, TiO2 represents titanium dioxide as a titanium source, BaTiO3 represents barium titanate, which is a target product, CO2 represents carbon dioxide, which is a by-product of the reaction, (s) represents solid state, (g) represents gaseous state, Δ represents high-temperature reaction, and the reaction temperature is ≥ 1100 ℃.

3. The multiphase composite wrapped high dielectric constant ceramic material of claim 1, wherein: The lead magnesium niobate is prepared from lead oxide, magnesium oxide and niobium pentoxide, and the chemical reaction formula is as follows: PbO (S) +MgO (S) +Nb2O 5(S) Pb( )O 3(S) wherein Nb2O5represents niobium pentoxide as a niobium source, MgO represents magnesium oxide as a magnesium source, PbO represents lead oxide as a lead source, PbO3represents lead magnesium niobate as a target product, (s) represents a solid state, Δ represents a solid phase reaction, and the reaction temperature is between 850 and 900 °C. wherein Nb2O5represents niobium pentoxide as a niobium source, MgO represents magnesium oxide as a magnesium source, PbO represents lead oxide as a lead source, PbO3represents lead magnesium niobate as a target product, (s) represents a solid state, Δ represents a solid phase reaction, and the reaction temperature is between 850 and 900 °C.

4. The multiphase composite wrapped high dielectric constant ceramic material of claim 1, wherein: The glass powder is a borosilicate glass, softening point = 650-750°C, thermal expansion coefficient = 4.5-5.5 x 10 -6 / K, with a particle size between 0.5 and 3 μm.

5. The multiphase composite wrapped high dielectric constant ceramic material of claim 1 wherein: The lanthanide elements are composed of lanthanum oxide, neodymium oxide and praseodymium oxide in a ratio of 1:1:

2.

6. A method of making a multiphase composite wrapped high dielectric constant ceramic material, characterized by, The composition and mass ratio of the multi-phase composite wrapped high dielectric constant ceramic material according to claim 1 are prepared by the following preparation steps: Step one, preparing the formula composition: preparing the formula proportion of barium titanate, strontium titanate, holmium oxide, lead magnesium niobate, titanium dioxide, yttrium oxide, magnesium oxide, bismuth oxide, lithium carbonate, silicon dioxide, zinc oxide, manganese dioxide, copper oxide, glass powder, lanthanide elements and binder; Step two, component pretreatment: pretreating the barium titanate, strontium titanate, lead magnesium niobate, titanium dioxide and glass powder; Step three, ball milling mixing: putting the pretreated barium titanate, strontium titanate, lead magnesium niobate, titanium dioxide and glass powder, and the formula proportion of holmium oxide, yttrium oxide, magnesium oxide, bismuth oxide, lithium carbonate, silicon dioxide, zinc oxide, manganese dioxide, copper oxide and lanthanide elements into a ball mill, adding 30%-40% of deionized water as a dispersion medium based on the total mass of all solid materials, then adding the binder at a rate of 10-15 mL / min, setting the ball-to-material ratio and ball milling time for ball milling, so that all components are fully mixed and uniform, to obtain a mixed slurry; Step four, drying and sieving: putting the mixed slurry after ball milling into a drying device for drying at a set temperature to obtain dried mixed powder, and sieving the dried powder; Step five, forming: putting the sieved mixed powder into a mold for pressing under a set condition to obtain a formed ceramic body; Step six, sintering: putting the formed ceramic body into a sintering furnace for sintering under a set condition to form a ceramic material; Step seven, post-processing: performing cutting, grinding and polishing post-processing on the sintered ceramic material, and then testing the performance of the ceramic material.

7. The multiphase composite wrapped high dielectric constant ceramic material and the method of making thereof according to claim 6, wherein: In the second step, the barium titanate and strontium titanate are pretreated by calcining at 850-900℃ for 2-3h; the lead magnesium niobate is calcined at 750-800℃ for 1-2h; the titanium dioxide is calcined at 550-600℃ for 1-2h; and the glass powder is dried at 100-120℃ for 4-6h.

8. The multiphase composite wrapped high dielectric constant ceramic material and the method of making thereof according to claim 6, wherein: In the third step, the ball milling conditions are as follows: zirconia balls are used as the grinding medium, the ball-to-material ratio is 5:1-8:1, the ball milling speed is 300-500r / min, and the ball milling time is 6-10h; the slurry is stirred every 1-2h during the ball milling; and the solid content of the slurry is controlled at 60%-70% after the ball milling.

9. The multiphase composite wrapped high dielectric constant ceramic material and the method of making thereof according to claim 6, wherein: In the fourth step, the drying and sieving conditions are as follows: the drying temperature is 80-120℃, the drying time is 10-14h, the vacuum drying is used, the vacuum degree is controlled at 0.08-0.1MPa, and the dried powder is sieved through a 100-150 mesh sieve.

10. The multiphase composite wrapped high dielectric constant ceramic material and the method of making thereof according to claim 6, wherein: In the fifth step, the forming conditions are as follows: the dry pressing method is used, the forming pressure is 150-200MPa, and the pressure holding time is 8-15min; the mold material is high-strength steel with a tensile strength of ≥600MPa, and 0.05-0.1g / dm² of zinc stearate is applied on the inner wall of the mold; the green compact density is 73%-74% after the forming; In the sixth step, the sintering conditions are as follows: the sintering temperature is 1300-1350℃, the sintering holding time is 3-4h, the heating rate is controlled at 5-8℃ / min, the oxygen atmosphere is maintained in the furnace during the sintering, the oxygen flow rate is 0.5-1L / min, and the temperature is decreased to room temperature at a rate of 3-5℃ / min after the sintering.

Citation Information

Cited By

  • Base metal high-voltage multilayer ceramic dielectric capacitor and ceramic dielectric material and preparation method thereof

    CN122102677A